2021
DOI: 10.1089/neu.2020.7144
|View full text |Cite
|
Sign up to set email alerts
|

Routinely Measured Hematological Markers Can Help to Predict American Spinal Injury Association Impairment Scale Scores after Spinal Cord Injury

Abstract: Neurological outcomes following spinal cord injury (SCI) are currently difficult to predict. While the initial American Spinal Injury Association Impairment Scale (AIS) grade can give an estimate of outcome, the high remaining degree of uncertainty has stoked recent interest in biomarkers for SCI. This study aimed to assess the prognostic value of routinely measured blood biomarkers by developing prognostic models of AIS scores at discharge and 12 months post-injury. Routine blood and clinical data were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 60 publications
(25 reference statements)
1
10
0
Order By: Relevance
“…delay to surgery). Only few studies investigated predictors such as blood measures, [59] magnetic resonance imaging, [62] and sensor data [63] . These findings are in line with Wingbermühle et al [66] and Wartenberg et al , [67] which both identified gaps in the investigation of a broad range of possible predictors including biological and physical, as well as psychosocial measures, and especially in the use of directly observable predictors such as imaging, biomarkers, and genetics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…delay to surgery). Only few studies investigated predictors such as blood measures, [59] magnetic resonance imaging, [62] and sensor data [63] . These findings are in line with Wingbermühle et al [66] and Wartenberg et al , [67] which both identified gaps in the investigation of a broad range of possible predictors including biological and physical, as well as psychosocial measures, and especially in the use of directly observable predictors such as imaging, biomarkers, and genetics.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 2378 articles were retrieved through database searching and after screening the titles and abstracts of 1851 articles and the full-texts of 234 articles, seven eligible studies were identified for inclusion in the scoping review [57][58][59][60][61][62][63] . The corresponding flow diagram of the screening process is presented in Figure 1 .…”
Section: Study Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many clinical and scientific attempts have been made to better diagnose and to develop new treatments to improve the prognosis of individuals following a spinal cord injury (SCI). There is growing evidence that measures of some haematological indices post-injury relate with longer term (12 month) clinical outcome measures in human SCI patients [1,2]. These studies indicate that over-time the 'whole-body', multi-organ response to SCI contributes to long-term clinical outcome and that proteins within the blood can be used to assess this phenomenon [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence that measures of some haematological indices post-injury relate with longer term (12 month) clinical outcome measures in human SCI patients [1,2]. These studies indicate that over-time the 'whole-body', multi-organ response to SCI contributes to long-term clinical outcome and that proteins within the blood can be used to assess this phenomenon [1,2]. Therefore a better understanding of the longitudinal protein changes within the blood following a SCI is needed to develop novel interventions [3].…”
Section: Introductionmentioning
confidence: 99%